2021
DOI: 10.1016/j.eats.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute Primary Repair of the Anterior Cruciate Ligament With Anterolateral Ligament Augmentation

Abstract: Acute injuries of the anterior cruciate ligament are often associated with concurrent injuries to the structures of the anterolateral complex, specifically the anterolateral ligament. Some injury patterns of the anterior cruciate ligament involve tearing of the majority of the ligament from the femoral origin, leaving a large, viable ligament remnant. In these patients, a repair of the anterior cruciate ligament back to the femoral origin can be undertaken. Subsequently, percutaneous repair of the anterolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Augmentation techniques have emerged as a procedure for enhancing ACL reconstruction success [1,14,18]; they were applied both in ACL-R [46][47][48] and ACL repair [1,14,18,19]. In the ACL repair setting, they follow the same principles and indications as in ACL-R [46,47].…”
Section: Augmentation Procedures With Acl Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Augmentation techniques have emerged as a procedure for enhancing ACL reconstruction success [1,14,18]; they were applied both in ACL-R [46][47][48] and ACL repair [1,14,18,19]. In the ACL repair setting, they follow the same principles and indications as in ACL-R [46,47].…”
Section: Augmentation Procedures With Acl Repairmentioning
confidence: 99%
“…Monaco et al have contributed to the field by presenting a specific technique that combines ACL repair with ALL suture augmentation, offering a comprehensive approach to addressing ligamentous laxity and rotational instability [19]. This technique underscores the importance of addressing both the primary ACL injury and potential deficiencies in the lateral structures of the knee to optimize overall joint stability and function.…”
Section: Laterally Based Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of direct suture repair of the ACL showed that 40% to 100% of cases ended in failure [8]. With the development of surgical techniques and devices, primary repair of acute ACL proximal tears with intact tibial remnants has attracted interest [9][10][11][12]. Although primary repair has advantages, it is not suitable for all types of ACL rupture [13].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Moreover, new techniques such as dynamic intraligamentary stabilization (DIS) which improves biological healing capacity and bridge-enhanced ACL repair (BEAR) grafts (with use of resorbable protein-based implant containing autologous blood to promote ligament healing) have shown encouraging results and renewed interest in the concept of primary repair of ACL. [7,15,[20][21][22][23][24][25][26][27] Some authors have speculated that the promising results of primary repair could lead to a shift away from ACL reconstruction and back to ACL repair but, so far, there has been no systematic review comparing these 2 methods for treatment of acute ACL injury. [14,28,29] Therefore, we performed this systematic review of randomized controlled trials (RCTs) to examine outcomes in patients undergoing primary ACL repair versus patients undergoing ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%